2018
DOI: 10.3382/ps/pey336
|View full text |Cite
|
Sign up to set email alerts
|

Xylo-oligosaccharides display a prebiotic activity when used to supplement wheat or corn-based diets for broilers

Abstract: It is now well established that exogenous β-1,4-xylanases improve the nutritive value of wheat-based diets for poultry. Among other factors, the mechanism of action of exogenous enzymes may involve a microbial route resulting from the generation of prebiotic xylo-oligosaccharides (XOS) in the birds' gastro-intestinal (GI) tract. In a series of three experiments, the effect of XOS on the performance of broilers fed wheat or corn-based diets was investigated. In experiment 1, birds receiving diets supplemented w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
78
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(85 citation statements)
references
References 52 publications
7
78
0
Order By: Relevance
“…Recent publications have suggested an alternative mechanism of action for XOS whether the prebiotic is supplemented in the diet or results from NSP hydrolysis. It has been suggested that XOS encourages the bacteria in the intestine to digest xylan, found in the feed, more efficiently and consequently increases nutrient digestion overall contributing to the improvements in animal performance [28]. If the microflora is encouraged to digest xylan more efficiently, this would explain the reduction in insoluble xylose and arabinose concentration in the ileum of broilers following the addition of carbohydrases or XOS to the diet.…”
Section: Discussionmentioning
confidence: 99%
“…Recent publications have suggested an alternative mechanism of action for XOS whether the prebiotic is supplemented in the diet or results from NSP hydrolysis. It has been suggested that XOS encourages the bacteria in the intestine to digest xylan, found in the feed, more efficiently and consequently increases nutrient digestion overall contributing to the improvements in animal performance [28]. If the microflora is encouraged to digest xylan more efficiently, this would explain the reduction in insoluble xylose and arabinose concentration in the ileum of broilers following the addition of carbohydrases or XOS to the diet.…”
Section: Discussionmentioning
confidence: 99%
“…FOS mixture produced by P. citreonigrum URM 4459 were analysed according to Nobre et al (2018c) and Ribeiro et al (2018). A mixture of commercial FOS Actilight ® (Beghin-Meiji Industries, France) was used as standard.…”
Section: Fos Identification and Quantificationmentioning
confidence: 99%
“…The injector and detector temperatures were 300 and 400°C, respectively. The flow rate of the carrier gas (H 2 ) was set at 1.7 mL/min (Ribeiro et al, 2018).…”
Section: Fos Identification and Quantificationmentioning
confidence: 99%
“…(2019) , relatively low amounts of AXOS added to broiler diets can act as substrate for saccharolytic microbiota, which are known to obtain their energy from such carbohydrates, thereby resulting in the production of SCFA. However, the size of performance responses observed when AXOS was added in the diets could not be solely explained by the low amount of energy yielded from the SCFA produced upon AXOS fermentation ( Józefiak et al., 2004 , Ribeiro et al., 2018 ). In addition, it is doubtful whether the low amounts of AXOS added in the diets would generate a meaningful amount of SCFA to be able to stimulate associated microbiota-modulated effects such as gut hormone responses.…”
Section: Introductionmentioning
confidence: 97%
“…The beneficial effects of these AXOS on performance characteristics and the overall health status of broilers are already well documented and have been intensively investigated over the past 15 years. AXOS are well-known for their prebiotic potential across species ( Courtin et al., 2008b , Geraylou et al., 2012 , Yacoubi et al., 2017 , Ribeiro et al., 2018 ). They will selectively stimulate the growth of the health-related microbial species, for example, Bifidobacteria , and increase the short-chain fatty acid ( SCFA ) production in the hindgut.…”
Section: Introductionmentioning
confidence: 99%